CO2/SO2 emission reduction in CO2 shipping infrastructure - Awoyomi, Adeola; Patchigolla, Kumar; Anthony, Ben (Cranfield University, 2019)
Simulation table streams for the liquefaction cycle, the capture process and the diesel engine used in Aspen Plus.All graphs can be generated from the given streams.
Keywords: 'CCS'; 'Post-combustion capture (PCC) of CO2'; 'Chemical absorption'; 'On-board capture'; 'Carbon Capture Engineering (excl. Sequestration)'